Inter‐organ communication: a gatekeeper for metabolic health. (19th August 2019) - Castillo‐Armengol, Judit; Fajas, Lluis; Lopez‐Mejia, Isabel C
Abstract: Multidirectional interactions between metabolic organs in the periphery and the central nervous system have evolved concomitantly with multicellular organisms to maintain whole‐body energy homeostasis and ensure the organism's adaptation to external cues. These interactions are altered in pathological conditions such as obesity and type 2 diabetes. Bioactive peptides and proteins, such as hormones and cytokines, produced by both peripheral organs and the central nervous system, are key messengers in this inter‐organ communication. Despite the early discovery of the first hormones more than 100 years ago, recent studies taking advantage of novel technologies have shed light on the multiple ways used by cells in the body to communicate and maintain energy balance. This review briefly summarizes well‐established concepts and focuses on recent advances describing how specific proteins and peptides mediate the crosstalk between gut, brain, and other peripheral metabolic organs in order to maintain energy homeostasis. Additionally, this review outlines how the improved knowledge about these inter‐organ networks is helping us to redefine therapeutic strategies in an effort to promote healthy living and fight metabolic disorders and other diseases. Abstract : This review discusses communication and key messengers between peripheral metabolic organs and the central nervous system that crosstalk for the maintenance of whole body energy homeostasis in health and disease.